Hubungan Antara Konteks Pekerjaan dengan Stres Kerja pada Pekerja Logistik Pangan PT.X di Karawang - Tri Indra Adithia; Baiduri Widanarko (Pro Health Jurnal Ilmiah Kesehatan, 2019)
(Background) Job stress related to work is one of the main problems in occupational safety and health. Improving uncomfortable conditions can stress workers so as to increase worker welfare and increase complications and depression. Health problems are the cause of the absence of work to increase productivity in organizations or companies. Therefore the author agrees to do stress work, with the aim of knowing the working relationship with stressful work. (Method) This research was conducted by taking data directly through questionnaires and observations at the study site (Result) The results of the study show that from nine variables, namely working hours, workload, work design, job control and work environment, it can be seen that the control has a significant value compared to other variables with a sig value of 0.042. (Conclusion) From these results it can be concluded that the context of the work most related to stress on workers is job control.